2016
DOI: 10.1176/appi.ajp.2015.15060788
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience With High-Dosage Pramipexole in Patients With Treatment-Resistant Depressive Episodes in Unipolar and Bipolar Depression

Abstract: Depressive disorders are common, costly, and often chronic or recurrent. The Sequenced Treatment Alternatives to Relieve Depression (STAR*D) study revealed that more than 1 in 3 outpatients with major depressive disorder will not achieve symptomatic remission despite several attempts at monotherapy, augmentation, and/or combination treatment (1-3). The Systematic Treatment Enhancement Program for Bipolar Disorder (STEP-BD) study of over 2,000 outpatients with bipolar disorder found that adding antidepressants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 37 publications
5
43
1
1
Order By: Relevance
“…As a subset of treatment resistant depressed patients have elevated systemic inflammation that respond to drugs specifically targeting inflammation (Raison et al, 2013), and with recent reports of dopamine agonist medication such as pramipexole being effective in treatment resistant depression (Fawcett et al, 2016), there is further opportunity to systematically use drugs that modulate dopaminergic neurotransmission as antidepressant medication in depressed patients with elevated pre-treatment levels of inflammatory biomarkers.…”
Section: 0 Discussionmentioning
confidence: 99%
“…As a subset of treatment resistant depressed patients have elevated systemic inflammation that respond to drugs specifically targeting inflammation (Raison et al, 2013), and with recent reports of dopamine agonist medication such as pramipexole being effective in treatment resistant depression (Fawcett et al, 2016), there is further opportunity to systematically use drugs that modulate dopaminergic neurotransmission as antidepressant medication in depressed patients with elevated pre-treatment levels of inflammatory biomarkers.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Hence, our findings are consistent with the potential role of drugs modulating dopaminergic neurotransmission in treatment of depression. For example, application of pramipexole, a dopamine receptor agonist, was reportedly effective in a recent case series of treatment resistant depression patients (46), particularly those patients with elevated IL-17 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies to date have focused on compounds such as cyclooxygenase (COX) inhibitors or minocycline, (Raison et al, 2013b) COX inhibitors Mixed results in psychiatric patients (Köhler et al, 2014;Sommer et al, 2012) Minocycline Reduced negative symptoms in schizophrenia (Köhler et al, 2014;Sommer et al, 2012) DA synthesis L-DOPA Increased motivation in PD (Czernecki et al, 2002) BH4 Case reports: improves depressive/motor symptoms (Pan et al, 2011;Sato et al, 2014) SAMe Evidence of success as adjuvant in MDD (Papakostas et al, 2010;Sarris et al, 2014;Sarris et al, 2015) L-Methylfolate Evidence of success as adjuvant in MDD (Ginsberg et al, 2011;Godfrey et al, 1990;Papakostas et al, 2012;Shelton et al, 2015) DA receptors D2 agonists Successful adjuvant in unipolar and bipolar depression (Cassano et al, 2004;Cusin et al, 2013;Fawcett et al, 2016;Franco-Chaves et al, 2013) Adenosine A2A antagonists…”
Section: Therapies That Block Inflammationmentioning
confidence: 99%
“…In addition to compounds that may increase DA availability and release, adenosine (A2A) receptor antagonists, which are thought to facilitate the activation of DA D2 receptors, are efficacious in reversing decreased effort-based sucrose consumption after DA depletion with tetrabenazine (a vesicular monoamine transporter inhibitor) and after peripheral administration of IL-1β in rats (Chen et al, 2001;Collins et al, 2010;Nunes et al, 2014;Xie et al, 2009;Yohn et al, 2015). The DA receptor agonist, pramipexole, has been shown to block endotoxin-induced degeneration of nigrostriatal DA cells (Iravani et al, 2008), and has also demonstrated the efficacy in unipolar and bipolar patients with treatment-resistant depression (Cassano et al, 2004;Cusin et al, 2013;Fawcett et al, 2016;Franco-Chaves et al, 2013).…”
Section: Strategies To Facilitate Da Packaging and Release Or Da Recementioning
confidence: 99%